Konsep Pewahyuan Injil Kepada Paulus Menurut Surat Galatia 1:11-12 - Boyman Aspirasi Zebua (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
This article discusses the gospel revelation that Christ gave to Paul. Paul in this case, has been called by God since he was still in his mother's womb, he was called by God to spread the gospel to other nations. This study aims to discuss the process of Pulus receiving the revelation of the gospel based on Galatians 1:11-12. The writing method used in writing this article is the exegesis method in Galatians 1:11-12 as well as a literature review of various literature sources related to the topic under study. The results of the study show that Paul in receiving the gospel proved that he received the gospel and lived the gospel not from human will, but he received it from God's statement to him. God had chosen him and according to God's plan, Paul would be a great Apostle. In Galatians 1:11-12, this verse has correctly recorded that Paul had been called by God and this verse speaks that Paul had accepted it, because it was a divine commission that he should have carried out. Even though the false teachers were spreading the false gospel which was a mixture of law and grace at that time, Paul remained steadfast and maintained the truth of the gospel, because he had a principle of life, he realized that his existence as an Apostle was because of God's call to him, not by human will.